Cryptic Female Choice in Arthropods 2015
DOI: 10.1007/978-3-319-17894-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Female Choice in Crickets and Relatives (Orthoptera: Ensifera)

Abstract: In his pioneering work on cryptic female choice, Eberhard identified a wide range of mechanisms that potentially allow multiply-mated females to bias paternity in favour of certain types of male following the start of copulation. The aim of this chapter is to review critically the empirical evidence for a range of these mechanisms of cryptic female choice in crickets and relatives (Orthoptera: Ensifera), while taking into account coevolutionary interactions between the sexes. There is compelling evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…Although the present study provided mixed support for sexual selection hypotheses for genital evolution, experimental manipulations, in which either one or both titillators were removed, have provided some support for the role of cryptic female choice (Wulff et al 2015, Vahed 2015, Wulff and Lehmann 2016. The results of these manipulations indicated that correct stimulation by titillators is necessary for the proper insertion of the spermatophore and to avoid resistance by females during copulation (Wulff et al 2015(Wulff et al , 2017Wulff and Lehmann 2016).…”
Section: Discussionmentioning
confidence: 48%
“…Although the present study provided mixed support for sexual selection hypotheses for genital evolution, experimental manipulations, in which either one or both titillators were removed, have provided some support for the role of cryptic female choice (Wulff et al 2015, Vahed 2015, Wulff and Lehmann 2016. The results of these manipulations indicated that correct stimulation by titillators is necessary for the proper insertion of the spermatophore and to avoid resistance by females during copulation (Wulff et al 2015(Wulff et al , 2017Wulff and Lehmann 2016).…”
Section: Discussionmentioning
confidence: 48%
“…In some cricket species, there is compelling evidence that the female can bias the use of sperm from selected males by controlling not only the duration of attachment of an externally attached spermatophore, but also the uptake of sperm to the spermatheca (Vahed ). Whether or not the female can influence the discharge of sperm from spermatodoses as a further mechanism of cryptic female choice deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A little is also known about inter‐ and intra‐specific variation in the shape of males' titillators (Harz, ). Since these sclerotized genital appendices are used in female stimulation and spermatophore transfer, it would be also interesting to determine the possible role of this sexual trait in heterospecific female mate choice (Vahed, ; Wulff et al, ). The costs of heterospecific mating are particularly high if postmating barriers are complete (e.g., gametic incompatibility or zygotic mortality), and there is no chance of siring viable hybrids (Gröning & Hochkirch, ).…”
Section: Discussionmentioning
confidence: 99%
“…titillators (Harz, 1969). Since these sclerotized genital appendices are used in female stimulation and spermatophore transfer, it would be also interesting to determine the possible role of this sexual trait in heterospecific female mate choice (Vahed, 2015;Wulff et al, 2015).…”
Section: Discussionmentioning
confidence: 99%